SINERGITAS PROGRAM KKM DALAM MENINGKATKAN KUALITAS HIDUP MASYARAKAT : PENDEKATAN MULTISEKTOR DI BIDANG PENDIDIKAN, EKONOMI DAN KELEMBAGAAN DI DESA PASIRIPIS KECAMATAN SURADE KABUPATEN SUKABUMI: PENDEKATAN MULTISEKTOR DI BIDANG PENDIDIKAN, EKONOMI DAN KELEMBAGAAN DI DESA PASIRIPIS KECAMATAN SURADE KABUPATEN SUKABUMI - Melani, Arie Melani Purbasari (STISIP Widyapuri Mandiri Sukabumi, 2025)
Student Community Service Program (KKM) is a manifestation of the Tridharma Higher Education in the field of community service. Student Community Service Program is designed to enhance the skills of students in dealing with real-world job opportunities. In Indonesia, KKM has become one of the manifestations of the Tridharma Higher Education that are popular and effective in improving the quality of life for the community. The objective of this study is to evaluate the synergy between the program in enhancing the quality of life for the community. This study aims to explain how the program can be integrated with existing education, economics, and institutional systems, and contribute to the improvement of community quality of life. This study employs a case study approach using a multisectoral perspective in the fields of education, economics, and institutions in Desa Pasiripis, Sukabumi Regency. Datawas collected through interviews, observations, and data analysis to evaluate the synergy between program KKM in enhancing the quality of life for the community. The results of this study indicate that the synergy between Student Community ServiceProgram (KKM) has influenced the level of awareness among the community about the importance of education, economics, and institutions. Additionally, students who participate in Student Community Service Program (KKM) also exhibit an improvementin their skills to handle real-world job opportunities and enhance their quality of life. This study shows that the synergy between the Kuliah Kerja Mahasiswa program can be a significant factor in improving the quality of life for the community. Therefore, emphasis should be placed on implementing effective and efficient program to achieve the desired objectives. The study also indicates that a multisectoral approach can be aneffective strategy in enhancing the synergy between the program